Chronic idiopathic thrombocytopenic purpura in a child with Sanfilippo type A - Ramaraj, Karthik Prabhu; Natarajan, Suresh; KG, Ravikumar (International Journal of Contemporary Pediatrics, 2017)
Mucopolysaccharidoses (MPS) are a group of storage disorders with an autosomal recessive inheritance. Sanfilippo disease is a type of MPS which occurs due to deficiency of lysosomal enzymes involved in the lysosomal degradation of heparan sulphate. They can be categorized into four different types based on the enzymes involved namely heparin N-sulfatase (type A), alpha-N-acetylglucosaminidase (type B), acetyl-CoA-glucosaminide acetyltransferase (type C) and N-acetylglucosamine-6-sulfatase (type D) respectively. In this case report we present a six years follow up of a child confirmed to have Sanfilippo type A disease, who developed chronic Idiopathic Thrombocytopenic Purpura (ITP).